Susceptibility of Cutibacterium acnes to topical minocycline foam. (April 2020) - Sutcliffe, Joyce; McLaughlin, Robert; Webster, Guy; Read, Andrew F.; Drlica, Karl; Elliott, Russell; Stuart, Iain
Abstract: FMX101 4% minocycline foam (FMX101 4%) is a novel, topical minocycline formulation for treatment of acne vulgaris. We report that FMX101 4% had an MIC90 of 0.25 μg/ml and was ≥4-fold more active than comparator antimicrobials against a panel of 98 clinical Cutibacterium acnes isolates. The panel was diverse by clonal complex and sequence type, having 20 novel multi-locus sequence types including clonal complexes and sequence types associated with acne (CC1, CC3, and CC4; ST1 and ST3). Some isolates were phenotypically resistant to clindamycin (6.1%), erythromycin (14.3%), and tetracycline (2.0% intermediate resistance). Six isolates (6.4%) carried a mutation in the quinolone resistance-determining region of gyrA . With C. acnes, spontaneous resistance to FMX101 4% occurred at frequencies ranging from ≤5 × 10 −9 to <1 × 10 −8 ; mutations were identified in rpsJ, a gene encoding 30S ribosomal protein S10. No mutant exhibited a minocycline MIC above 0.5 μg/ml. No second-step mutation in previously isolated mutants or strains containing rpsJ ± 16S rRNA mutations was detected following minocycline challenge. Minocycline retained antibacterial activity against C. acnes over 15 multiple passages; thus, no selective growth advantage for minocycline-resistant mutants occurred under the experimental conditions. FMX101 4% has the potential to retain the favorable resistance profile of minocycline in diverse C. acnes isolates while providing the benefits of a topical formulation for treatment of acne vulgaris. Highlights: FMX101 4% was ≥4x more active than 8 comparator antimicrobials against C. acnes. The frequency of spontaneous resistance to FMX101 4% was low at <1 × 10 −8 . Potent antibacterial activity against C. acnes maintained over 15 serial passages. No selective growth advantage was observed for minocycline-resistant mutants.